Human Y chromosome phylogenetics and phylogeography - Underhill, Peter (Henry Stewart Talks, 2007)
Framework of human genetic variation, Locus specific forces vs. population level forces, Y chromosome DNA sequence variation, Genetic memory, Phylogenetics, principles and characteristics, Out of Africa, Y chromosome phylogeography, Recovering population histories
Archived at 2021/02/25